Gluten Intolerance: Sex- and Age-Related Features - MJ Llorente-Alonso; MJ Fernández-Aceñero; M Sebastián (Canadian Journal of Gastroenterology)
OBJECTIVE: Gluten intolerance is an immune-mediated enteropathy associated with gluten-containing foods in genetically susceptible patients. The typical form mainly affecting children shows failure to thrive and/or gastrointestinal symptoms. The adult form is less typical, presenting vague gastrointestinal symptoms, iron deficiency (with or without anemia) or nonspecific serum chemistry abnormalities. The present study aims to analyze clinical and biochemical differences of celiac disease (CD) according to sex and age.